2012
DOI: 10.1177/0748730412441172
|View full text |Cite
|
Sign up to set email alerts
|

Does Pupil Constriction under Blue and Green Monochromatic Light Exposure Change with Age?

Abstract: Many nonvisual functions are regulated by light through a photoreceptive system involving melanopsin-expressing retinal ganglion cells that are maximally sensitive to blue light. Several studies have suggested that the ability of light to modulate circadian entrainment and to induce acute effects on melatonin secretion, subjective alertness, and gene expression decreases during aging, particularly for blue light. This could contribute to the documented changes in sleep and circadian regulatory processes with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
53
0
1

Year Published

2012
2012
2025
2025

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 53 publications
(65 citation statements)
references
References 54 publications
(82 reference statements)
11
53
0
1
Order By: Relevance
“…This indicates the possibility that the contribution of mRGC to nocturnal melatonin suppression was promoted by high transmittance of the crystalline lens in children, particularly for a short wavelength light (Boettner and Wolter 1962; Barker et al 1991). Nonetheless, in terms of the effects of age-related ocular alteration on physiological functions, there is still a lack of agreement among previous studies (Herljevic et al 2005;Daneault et al 2012;Higuchi et al 2014;Najjar et al 2014;Gimenez et al 2016). According to a recent report, pre-to mid-pubertal children showed significantly greater melatonin suppression than that in children in the late to post-pubertal group (Crowley et al 2015) although there might be no large difference in lens transmittance or pupil size between the two groups (Barker et al 1991;Winn et al 1994), indicating factors other than ophthalmologic characteristics might be involved in the higher sensitivity to evening light in pre-to mid-pubertal children.…”
Section: Discussionmentioning
confidence: 96%
“…This indicates the possibility that the contribution of mRGC to nocturnal melatonin suppression was promoted by high transmittance of the crystalline lens in children, particularly for a short wavelength light (Boettner and Wolter 1962; Barker et al 1991). Nonetheless, in terms of the effects of age-related ocular alteration on physiological functions, there is still a lack of agreement among previous studies (Herljevic et al 2005;Daneault et al 2012;Higuchi et al 2014;Najjar et al 2014;Gimenez et al 2016). According to a recent report, pre-to mid-pubertal children showed significantly greater melatonin suppression than that in children in the late to post-pubertal group (Crowley et al 2015) although there might be no large difference in lens transmittance or pupil size between the two groups (Barker et al 1991;Winn et al 1994), indicating factors other than ophthalmologic characteristics might be involved in the higher sensitivity to evening light in pre-to mid-pubertal children.…”
Section: Discussionmentioning
confidence: 96%
“…To account for age-dependent differences, we normalized PLR responses to dark-adapted pupil size, i.e. we determined percentage pupillary constriction, which is stable across age groups (Birren et al, 1950; Daneault et al, 2012). In doing so, we found that the sensitivity of pupillary responses in the blind individual was similar to mice without rod-cone function (Lucas et al, 2003; Do et al, 2009) and macaques with pharmacologic blockade of synaptic input to ipRGCs (Gamlin et al, 2007); hence we consider it unlikely that age-related decline in sympathetic or retinal function contributed substantially to differences we observed in pupillary responses between sighted individuals and the older blind patient.…”
Section: Discussionmentioning
confidence: 99%
“…Daneault and colleagues tested whether this impacts response to monochromatic light exposure. They found that while older adults had smaller pupils at dark-adapted baseline and at all light levels tested, the reduction in pupil size in response to light was not different between young and older subjects [136]. Thus, available evidence suggests that light transmission through the lens is altered with age, specifically reducing transmission of short wavelength light.…”
Section: Evidence For Circadian Changes In Aging In Humansmentioning
confidence: 99%